Peningkatan Hasil Pembelajaran Tematik Terpadu Menggunakan Model Cooperative Learning Tipe Make A Match - Risna Muliani; Mansurdin Mansurdin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2021)
This study aims to describe the increase in learning outcomes in integrated thematic learning using the Cooperative Learning model Make A Match type V in elementary school. This type of research is Classroom Action Research (CAR) that uses qualitative and quantitative approaches. The subjects of this study were 25 elementary school teachers and students. The results showed planning, implementation and learning outcomes have increased. The average assessment of RPP cycle I was 84.89% with qualifications (B) and in cycle II it increased to 93.18% (A). The average evaluation of the implementation of the activities of the first cycle teacher is 83.93% (B) and increased in the second cycle is 92.86% (A). For the average activity of students in cycle I 82.18% (B) increased in cycle 92.86% (A). The average assessment of student learning outcomes for students in the first cycle was 79.95 (C) and increased in the second cycle was 92.40 (A).